Synthesis, characterization and evaluation of transfection efficiency of dexamethasone conjugated poly(propyleneimine) nanocarriers for gene delivery# - Bizhan Malaekeh-Nikouei; Mehdi Rezaee; Leila Gholami; Naghmeh Sanjar Mousavi; Reza Kazemi Oskuee (Taylor & Francis Group, 2018)
Context: Polypropylenimine (PPI), a cationic dendrimer with defined structure and positive surface charge, is a potent non-viral vector. Dexamethasone (Dexa) conveys to the nucleus through interaction with its intracellular receptor. Objective: This study develops efficient and non-toxic gene carriers through conjugation of Dexa at various percentages (5, 10 and 20%) to the fourth and the fifth generation PPIs (PPIG4s and PPIG5s). Materials and methods: The 21-OH group of Dexa (0.536 mmol) was modified with methanesulfonyl chloride (0.644 mmol) to activate it (Dexa-mesylate), and then it was conjugated to PPIs using Traut's reagent. After dialysis (48 h) and lyophilization, the physicochemical characteristics of products (PPI-Dexa) including zeta potential, size, buffering capacity and DNA condensing capability were investigated and compared with unmodified PPIs. Moreover, the cytotoxicity and transfection activity of the Dexa-modified PPIs were assessed using Neuro2A cells. Results: Transfection of PPIG4 was close to PEI 25 kDa. Although the addition of Dexa to PPIG4s did not improve their transfection, their cytotoxicity was improved; especially in the carrier to DNA weight ratios (C/P) of one and two. The Dexa conjugation to PPIG5s enhanced their transfection at C/P ratio of one in both 5% (1.3-fold) and 10% (1.6-fold) Dexa grafting, of which the best result was observed in PPIG5-Dexa 10% at C/P ratio of one. Discussion and conclusions: The modification of PPIs with Dexa is a promising approach to improve their cytotoxicity and transfection. The higher optimization of physicochemical characteristics, the better cell transfection and toxicity will be achieved.